2007
DOI: 10.1074/jbc.m703310200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase-independent Non-genomic Signals Transit from the Androgen Receptor to Akt1 in Membrane Raft Microdomains

Abstract: The serine-threonine kinase, Akt1/protein kinase B␣ is an important mediator of growth, survival, and metabolic signaling. Recent studies have implicated cholesterol-rich, lipid raft microdomains in survival signals mediated by Akt1. Here we address the role of lipid raft membranes as a potential site of intersection of androgenic and Akt1 signaling. A subpopulation of androgen receptor (AR) was found to localize to a lipid raft subcellular compartment in LNCaP prostate cancer cells. Endogenous AR interacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 42 publications
5
57
0
1
Order By: Relevance
“…These studies suggest a mechanism of signal downregulation of IRS-1 that is mediated by monomeric p85 through the formation of a sequestration complex between p85 and IRS-1 ( 187 ). Modulation of PI3K-Akt signaling components in the membrane raft microdomains have been reported (188)(189)(190). Consistent with these reports, we have also demonstrated the localization of the IR and PI3K in detergentresistant membrane rafts of rod photoreceptor outer segments ( 191 ).…”
Section: Pi3k Knockout Phenotypessupporting
confidence: 90%
“…These studies suggest a mechanism of signal downregulation of IRS-1 that is mediated by monomeric p85 through the formation of a sequestration complex between p85 and IRS-1 ( 187 ). Modulation of PI3K-Akt signaling components in the membrane raft microdomains have been reported (188)(189)(190). Consistent with these reports, we have also demonstrated the localization of the IR and PI3K in detergentresistant membrane rafts of rod photoreceptor outer segments ( 191 ).…”
Section: Pi3k Knockout Phenotypessupporting
confidence: 90%
“…In this study, we showed that ␤2M mAb inhibited a large number of cell signaling networks, including MAPK, SREBP-1, AR, and PI3K/Akt. It is conceivable that these signaling networks are interconnected through lipid raft complexes (47,48). The inhibitory action exerted by ␤2M mAb could affect the lipid composition of the raft structures, hence altering domain interactions and how downstream cell signal networks can be assembled and interact in a coordinated manner (45,49).…”
Section: Discussionmentioning
confidence: 99%
“…However, we (Liao et al, 2004) and other (Mellinghoff et al, 2004) found that Src kinase inhibitor did not suppress androgen-induced gene expression, indicating that Src kinase is not involved in androgen-induced PI3K activation or AR genomic effect. In addition, recent studies showed that after androgen stimulation the AR was transiently translocated to the lipid rafts on the plasma membrane (Lu et al, 2001;Cinar et al, 2007), where multiple signaling molecules such as G proteins are located (reviewed in Chini and Parenti, 2004). In fact, G protein a-subunit has been shown to activate the AR in the absence or presence of androgens (Kasbohm et al, 2005).…”
Section: Discussionmentioning
confidence: 99%